1993
DOI: 10.1007/bf01246453
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and severe brain damage: preliminary data

Abstract: Severe brain damage may cause alterations of cardiovascular function: heart rate, particularly, require the integrity of the vagal, sympathetic and central nervous systems. We studied brain-heart functional relation and neurovegetative modulation by spectral analysis of heart rate variability (HRV). This technique allows separate evaluation of the sympathetic and vagal components of heart rate modulation. In order to correlate changes in HRV with brain damage, we performed 45 recordings in 6 patients (5/1 M/F)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Studies by Crus-Rojas et al and Saucedo-Vence et al also reported that acesulfame K and sucralose increase the oxidative activity in the brain of common carp [ 5 , 80 ]. Heart rate is controlled by signals from the brain, therefore, damage in the brain may cause alterations in heart rate regulation [ 81 , 82 , 83 ]. A previous study in common carp also suggested lower antioxidant capacity after sucralose exposure [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Crus-Rojas et al and Saucedo-Vence et al also reported that acesulfame K and sucralose increase the oxidative activity in the brain of common carp [ 5 , 80 ]. Heart rate is controlled by signals from the brain, therefore, damage in the brain may cause alterations in heart rate regulation [ 81 , 82 , 83 ]. A previous study in common carp also suggested lower antioxidant capacity after sucralose exposure [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous study, zebrafish treated with saccharin also exhibited infiltration of inflammatory cells into zebrafish liver and brain by increasing cholesteryl ester transfer protein, which play an important role in transporting and exchange of cholesteryl ester to triglyceride and vice versa [20]. Heart rate is controlled by signals from the brain, therefore, damage in the brain may cause alterations in heart rate regulation [69][70][71].…”
Section: Saccharin Induces Distinct Cardiac Performance In Zebrafish mentioning
confidence: 94%